(4x-3)+(3x+2)=90

Simple and best practice solution for (4x-3)+(3x+2)=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x-3)+(3x+2)=90 equation:


Simplifying
(4x + -3) + (3x + 2) = 90

Reorder the terms:
(-3 + 4x) + (3x + 2) = 90

Remove parenthesis around (-3 + 4x)
-3 + 4x + (3x + 2) = 90

Reorder the terms:
-3 + 4x + (2 + 3x) = 90

Remove parenthesis around (2 + 3x)
-3 + 4x + 2 + 3x = 90

Reorder the terms:
-3 + 2 + 4x + 3x = 90

Combine like terms: -3 + 2 = -1
-1 + 4x + 3x = 90

Combine like terms: 4x + 3x = 7x
-1 + 7x = 90

Solving
-1 + 7x = 90

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 7x = 90 + 1

Combine like terms: -1 + 1 = 0
0 + 7x = 90 + 1
7x = 90 + 1

Combine like terms: 90 + 1 = 91
7x = 91

Divide each side by '7'.
x = 13

Simplifying
x = 13

See similar equations:

| 2x+2+2x+1+x+1=180 | | -q+3+2q-1-2=13+27-q+q | | 5.25t+5=16.5t+4 | | 3g+12-5g=22 | | t*4-8=10 | | 4x+3(2x-4)=0 | | -3y^3+4y^2+14y+6=0 | | -4y+8=4(2y-2)-2(-16-8y) | | a*3+1=13 | | 20x+8=8(3x+1) | | -7r-3+2r-1-1=13+17 | | 4x^2+4= | | 4y^2+14y-3y^3+6=0 | | 8(m+2)=4(5+2m) | | 2a+3+3a-1-2=7a+19-2a+16-5a | | a+14=1 | | a+14=-1 | | 3x-3(3+x)=4 | | 4x^2+1=2-5x | | 5a-7=5(a-2)+3 | | (7x-4)(9x+6)=0 | | 13+9x+1-5x=15x+3x | | 10=5(x+4) | | 2x+6=-4+-12 | | 10+5(z-2)=7z-8 | | 2x+3+x-9=90 | | 13=12+-5-3t | | 8+15=3p+12-5-p | | 5h+5u=p | | 24=30-0.6 | | y+c=15 | | w+4w=30-w |

Equations solver categories